Usability Test Results for a Discovery Tool in an Academic Library - Jody Condit Fagan; Meris A. Mandernach; Carl S. Nelson; Jonathan R. Paulo; Grover Saunders (Information Technology and Libraries, 2008)
Discovery tools are emerging in libraries. These tools offer library patrons the ability to concurrently search the library catalog and journal articles. While vendors rush to provide feature-rich interfaces and access to as much content as possible, librarians wonder about the usefulness of these tools to library patrons. In order to learn about both the utility and usability of EBSCO Discovery Service, James Madison University conducted a usability test with eight students and two faculty members. The test consisted of nine tasks focused on common patron requests or related to the utility of specific discovery tool features. Software recorded participants’ actions and time on task, human observers judged the success of each task, and a post-survey questionnaire gathered qualitative feedback and comments from the participants.  Overall, participants were successful at most tasks, but specific usability problems suggested some interface changes for both EBSCO Discovery Service and JMU’s customizations of the tool.  The study also raised several questions for libraries above and beyond any specific discovery tool interface, including the scope and purpose of a discovery tool versus other library systems, working with the large result sets made possible by discovery tools, and navigation between the tool and other library services and resources.  This article will be of interest to those who are investigating discovery tools, selecting products, integrating discovery tools into a library web presence, or performing evaluations of similar systems.